Talk, Text, and Tasks in Student-Initiated Instructional Interaction. Issue 8 (17th November 2017) - Åberg, Mikaela
Abstract : This study examines student-initiated instructional interaction in contexts where students work individually with tasks. The aim is to demonstrate some systematic ways in which the actions of students and teachers are contingent on, shaped by, and oriented to these tasks and the associated texts. Analyses of three encounters situated in different phases of the students' work are presented: in the beginning of the task, students ask open-ended questions about textual instructions and what they are supposed to do; in the midst of reading textbooks and writing texts, students ask the teacher to clarify or confirm some issue; and after having written a text, students request the teacher to read it, and assess whether it is acceptable or needs revision. The analyses show the interplay between talk, text, and task, and how the instructional interaction orients towards what the students have done before the encounters and what they should do next.